2019
DOI: 10.3390/polym12010021
|View full text |Cite
|
Sign up to set email alerts
|

Novel Siloxane-Modified Epoxy Resins as Promising Encapsulant for LEDs

Abstract: This study investigated a new category of transparent encapsulant materials for light-emitting diodes (LEDs). It comprised a phenyl group that contained siloxane-modified epoxy (SEP-Ph) hybridized with a cyclic tetrafunctional siloxane-modified epoxy (SEP-D4) with methylhexahydrophthalic anhydride (MHHPA) as a curing agent. The SEP-Ph/SEP-D4 = 0.5/0.5 (sample 3) and SEP-D4 (sample 4) could provide notably high optical transmittance (over 90% in the visible region), high-temperature discoloration resistance, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The acid anhydride curing agent relies on the hydroxyl group in the epoxy to open the ring of the acid anhydride to form a carboxylic acid, which further reacts with the epoxy group. At the same time, the hydroxyl group can also open the ring of the epoxy group to form a cross-linking network [ 34 ]. The reaction temperature between anhydride curing agent and epoxy resin is high.…”
Section: Reaction Mechanism Of Anhydride-cured Epoxy Resinmentioning
confidence: 99%
“…The acid anhydride curing agent relies on the hydroxyl group in the epoxy to open the ring of the acid anhydride to form a carboxylic acid, which further reacts with the epoxy group. At the same time, the hydroxyl group can also open the ring of the epoxy group to form a cross-linking network [ 34 ]. The reaction temperature between anhydride curing agent and epoxy resin is high.…”
Section: Reaction Mechanism Of Anhydride-cured Epoxy Resinmentioning
confidence: 99%
“…Therefore, the epoxy resin shell need proper light stabilizers or stable groups to deactivate the free radicals. As a result, the preparation of epoxy resin-coated QD is more complex, expensive, and time-consuming than that of the SiO 2 shell-coated [26,27]. The SiO 2 shell is usually generated by the hydrolytic polycondensation at ambient temperature, which is simple and economic.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on encapsulation materials, it was reported that silicone, 13 fluororesin, 14 siloxane‐modified epoxy resins, 15 diminish the abrupt change in refraction properties between the semiconductor and air, generating a larger light‐escape cone. However, these transparent encapsulation materials display a refractive index of about 1.35–1.50, which is still much smaller than those of III–V phosphides and nitrides.…”
Section: Introductionmentioning
confidence: 99%